(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Diversity and distribution of obligate parasitic fungi belonging to the orders Albuginales, Erysiphales, Peronosporales and Pucciniales on the territory of eight parks and six public gardens of Odessa have been studied. As a result 80 species have been found, among them three species belonged to Albuginales, 39 – to Erysiphales, 22 – to the Peronosporales and 16 species to the Pucciniales. These fungi parasitized 108 species of host plants belonging to 91 genera and 40 families. The list of recorded fungi and their hosts is presented.